TEACHER'S DIRECTIVE SPEECH ACTIONS IN THE TEACHING AND LEARNING PROCESS AT KARYA PUTRA KINDERGARTEN - Abd. Rahim (Research and Development Journal of Education, 2022)
This article was written to describe the form of directive speech acts that teachers use during the teaching and learning process, as well as to describe the teacher's speech act strategies that were utilized during the teaching and learning process at Karya Putra Babakan Sari Kindergarten in Bandung. This research utilizes the directed speech acts of kindergarten instructors as its primary source of data. At Karya Putra Kindergarten, the most important source of information is the teacher's actual words and actions. The data was gathered through the use of observation techniques, as well as recording and note-taking procedures as an advanced way. The findings from the teaching and learning exchanges that took place at Karya Putra Kindergarten reveal that there are five distinct sorts of speech acts that instructors engage in. These speech acts include ordering, begging, demanding, advising, and challenging students. In the meanwhile, researchers discovered that directive speech acts can serve four distinct functions: advice, inquiries, instructions, and requests. In addition, the study discovered that pupils engaged in two distinct varieties of directive speech acts, namely pleading and demanding. In spite of the fact that there are two functions, requests and inquiries